The Typification of the Regions of Ukraine by Possibilities for Sustainable Waste Management - Кононенко, Олена Юріївна; Молодика, В. (Київський національний університет імені Тараса Шевченка, 2019)
Sustainable waste management is an urgent task for modern science and management practice. The search for effective governance mechanisms within the framework of this study was performed in accordance with the concept of sustainable development and circular economy. The transition to a sustainable waste management model is considered as an advancing process to increase the part of mass production and consumption waste which is returned to the manufacturing cycle. In this regard, the assessment of sustainable waste management in the regions should include the dynamics indicators on the main components of waste management. The methodology of this study is based on the generalization of sustainable waste management indicators, which have been analyzed at a certain point in time and in the dynamics as well. The regions of the country were grouped by waste management efficiency. The selected four groups of regions are located rather compact, they have common features in terms of production profile and waste structure. The typification of the regions of Ukraine was developed on the basis of grouping, as well as taking into account the specialization of regions in one or a few main industries, levels of urbanization of these regions. Five types of regions were identified: two types with a high share of municipal waste, regions with a predominance of industrial waste, and two types of industrial-agrarian regions where the waste of different types is generated with a significant share of agricultural waste. Regions of the same type are typically characterized by the similarity of waste management issues. These can be both traditional problems of accumulating large quantities of waste in landfills, as well as new challenges related to population migration, the formation of new administrative units (united territorial communities), which change the functioning of the current system of waste management. Significant differences in the main waste management indicators for different types require the use of similar (typical) approaches to the development of regional strategies and regional waste management plans.

Стале управління відходами є актуальним завданням як для сучасної науки, так і для управлінської практики. Пошук ефективних механізмів управління в рамках даного дослідження здійснено відповідно до концепції сталого розвитку та циркулярної економіки. Перехід до моделі сталого управління відходами розглядається як поступальний процес зростання частки відходів виробництва та споживання, що повертаються до виробничого циклу. У зв’язку з цим,оцінка сталого управління відходів в регіонах має включати індикатори динаміки щодо основних складових управління відходами. Методика даного дослідження ґрунтується на узагальненні показників сталого поводження з відходами, що були проаналізовані станом на певний момент часу, а також у динаміці. Було проведено групування регіонів країни за ефективністю управління відходами. Виділені чотири групи регіонів мають чітко виражену територіальну прив’язку, спільні риси щодо виробничого профілю та структури утворених відходів. Типізація регіонів України розроблена на основі групування, а також з урахуванням спеціалізації регіонів у загальнонаціональному поділі праці, рівнів урбанізації регіонів. Було виділено п’ять типів регіонів: два типи з високою часткою побутових відходів, регіони з переважанням промислових відходів та два типи індустріально-аграрних регіонів, що мають змішану структуру відходів, з суттєвою часткою відходів сільського господарства. Для регіонів одного типу, як правило, характерним є схожість проблем щодо поводження з відходами. Це можуть бути як традиційні проблеми накопичення великої кількості відходів у місцях їх зберігання та захоронення, так і нові виклики, пов’язані з міграцією населення, утворенням нових адміністративних одиниць (об’єднаних територіальних громад), що вносять зміни в функціонування діючої системи поводження з відходами. Суттєві відмінності щодо основних показників поводження з відходами для різних типів вимагають використання подібних (типових) підходів до розроблення регіональних стратегій та регіональних планів управління відходами.
Типізація регіонів України за можливостями сталого управління відходами
Довкілля України за 2017 рік. Статистичний збірник. – К.: Державна служба статистики України, 2018 – 225 с. Мезенцев К.В., Підгрушний Г.П., Мезенцева Н.І. Регіональний розвиток в Україні: суспільно-просторова нерівність і поляризація: Монографія. – К.: ДП «Прінт Сервіс», 2014. – 132 с. Моніторинг озеленення економіки при реалізації угоди про асоціацію Україна – ЄС. Аналітична доповідь. – // Електронний ресурс. – Режим доступу: https://www.civic-synergy.org.ua/wp-content/uploads/2018/04/Monitoryng-ozelenennya-ekonomiky-pry-realizatsiyi-Ugody-pro-asotsiatsiyu-Ukrayina-YES.pdf Стан сфери поводження з побутовими відходами в Україні за 2016 та 2013 роки. Міністерство розвитку громад та територій України // Електронний ресурс. – Режим доступу: http://www.minregion.gov.ua/napryamki-diyalnosti/zhkh/terretory/stan-sferi-povodzhennya-z-pobutovimi-vidhodami-v-ukrayini-za-2016-rik/ Стратегія сталого розвитку України до 2030 року. Проект 2017 // Електронний ресурс. – Режим доступу: http://www.ua.undp.org/content/ukraine/uk/home/library/sustainable-development-report/Sustainable-Dev-Strategy-for-Ukraine-by-2030.html Andersen M.S. An introductory note on the environmental economics of the circular economy // Sustainability Science – 2007. – № 2, P. 133–140. Banaitė, D., Tamošiūnienė, R. Sustainable development: the circular economy indicators’ selection model // Journal of Security and Sustainability Issues. – 2016. – № 6(2).- P. 315–323. Burton, C.H., Turner C. Manure Management: Treatment Strategies for Sustainable Agriculture. 2nd / Silsoe: Silsoe Research Institute, 2003 – 451 p. Georgeson, Maslin M., Poessinouw M. The global green economy: a review of concepts, definitions, measurement methodologies and their interactions Geo: Geography and Environment. – 2017. – № 4 (1) // Електронний ресурс. – Режим доступу: https://rgs-ibg.onlinelibrary.wiley.com/doi/pdf/10.1002/geo2.36 Global indicator framework adopted by the General Assembly (A/RES/71/313) including annual refinements contained in E/CN.3/2018/2 (Annex II) and E/CN.3/2019/2 (Annex II). – // Електронний ресурс. – Режим доступу:https://unstats.un.org/sdgs/indicators/Global%20Indicator%20Framework%20after%202019%20refinement_Eng.pdf Heeres, R.R., Vermeulen, W.J.V., deWalle, F.B Eco-industrial park initiatives in the USA and the Netherlands :first lessons // Journal of Cleaner Production.- 2004. – № 12 (8–10), 985–995. Lewandowski, M. Designing the Business Models for Circular Economy // Sustainability. – 2016. – №. 8(1), 1-28. Mendes, Santos A., Nunes L., Teixeira M. Evaluating municipal solid waste management performance in regions with strong seasonal variability // Ecological Indicators. – 2013. – № 30. – P. 170–177. Nilsson-Djerf, J., McDougall, F. Social factors in sustainable waste management // Warmer Bulletin. – 2000. – № 73. – P. 18–20. Sustainable development in the European Union: Monitoring report on progress towards the SDGs in an EU 2018 edition – Luxembourg: Publications Office of the European Union, 2018. – 356 р. The Global Waste Management Outlook // Електронний ресурс. – Режим доступу: https://www.uncclearn.org/sites/default/files/inventory/unep23092015.pdf Towards The Circular Economy Vol. 1: An Economic And Business Rationale For An Accelerated Transition. Ellen MacArthur Foundation. 2013.- // Електронний ресурс. – Режим доступу: https://www.ellenmacarthurfoundation.org/assets/downloads/publications/Ellen-MacArthur-Foundation-Towards-the-Circular-Economy-vol.1.pdf Tracking progress on Sustainable Development Goals for the regions of Ukraine: choosing indicators and setting baselines. – Kyiv, 2019. – 270 P. – // Електронний ресурс. – Режим доступу: http://www.ua.undp.org/content/ukraine/uk/home/library/sustainable-development-report/tracking-progress-on-SDGs-for-the-regions-of-Ukraine.html?fbclid=IwAR06_0XRAoHKq-u3JNXuyI0ot9sP4roY6OLrFQ2Ik6JbvF6w-uh745Z7vXk Waste prevention in Europe – policies, status and trends in reuse in 2017. EEA Report No 4/2018/ – // Електронний ресурс. – Pежим доступу: https://www.eea.europa.eu/publications/waste-prevention-in-europe-2017
Keywords: відходи; сталий розвиток; циркулярна економіка; ефективність управління відходами; типізація; waste; sustainable development; circular economy; waste management efficiency; typification